2012
DOI: 10.1537/asj.120709
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness and methodological validity of the study of musculoskeletal stress markers for the reconstruction of past human activities and life-styles

Abstract: (平成 23 年 9 月 22 日受付,平成 24 年 7 月 9 日受理) キーワード:筋骨格ストレスマーカー,生業・生活様式,活動パターン,吉母浜漁撈民,江戸時代武士The usefulness and methodological validity of the study of musculoskeletal stress markers for the reconstruction of past human activities and life-styles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 47 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Use of the scoring method of Hawkey and Merbs is also appropriate in this study because it allows for the ranking of data with respect to entheseal severity. Finally, previous research involving Japanese samples has produced reliable results utilizing the scoring method of Hawkey and Merbs (Yonemoto, ). The author of this study collected all data used in the following analyses, thereby minimizing subjective variation in scoring.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Use of the scoring method of Hawkey and Merbs is also appropriate in this study because it allows for the ranking of data with respect to entheseal severity. Finally, previous research involving Japanese samples has produced reliable results utilizing the scoring method of Hawkey and Merbs (Yonemoto, ). The author of this study collected all data used in the following analyses, thereby minimizing subjective variation in scoring.…”
Section: Methodsmentioning
confidence: 99%
“…The author of this study collected all data used in the following analyses, thereby minimizing subjective variation in scoring. By examining correlations between the entheseal changes of individuals from differing social classes during the Edo period using the scoring method of Hawkey and Merbs, Yonemoto () demonstrated that individuals known to be members of the samurai class shared similarities that could not be seen in non‐ samurai individuals in terms of their profiles of enthseal change. These results indicated the methodological validity of the scoring method of Hawkey and Merbs, and demonstrated its usefulness in the reconstruction of past human activities and lifestyles.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations